Fatigue crack growth investigation on offshore pipelines with three-dimensional interacting cracks - Zhang, Yanmei (2018)
Due to high cost of full-scale experimental setup, this study presents a numerical model on fatigue behaviours of offshore pipeline with multiple coplanar cracks under cyclic tensile loadings. The validation on numerical results is made by other researchers' experimental results, and significant parameters affecting fatigue crack growth are studied.